Causes of financial distress following leveraged recapitalizations - Denis, David J.; Denis, Diane K. (Journal of Financial Economics, 1995)
We report that 31% of the firms completing leveraged recapitalizations between 1985 and 1988 subsequently encounter financial distress. Following their recaps, the distressed firms exhibit (1) poor operating performance due largely to industry-wide problems, (2) surprisingly low proceeds from asset sales, and (3) negative stock price reactions to economic and regulatory events associated with the demise of the market for highly-leveraged transactions. The incidence of distress is not related to several characteristics that have previously been linked with poorly-structured deals. We thus attribute the high rate of distress primarily to unexpected macroeconomic and regulatory developments.